Practice and reflection of differentiated learning in sociology at senior high school - Hati, Kusuma; Rahmayanti, Ayu Afriliani; Aprilia, Cinta Widi Happy; An Nisa, Luthfiyah; Anggraeni, Meisita; Trinugraha, Yosafat Hermawan; Parahita, Bagas Narendra (Journal of Education and Learning (EduLearn), 2025)
Global challenges require the government to organize learning in schools that are more up-to-date following episodes in the times. The independent curriculum learning promises flexibility for teachers and students and replaces the relatively new curriculum-13. In implementing the independent curriculum, differentiated learning is a concept that focuses on the diversity of students’ learning styles. This research was conducted to obtain an overview of the implementation and reflection of differentiated learning in senior high schools in Central Java. Teachers, especially those teaching sociology subjects, the assistant principal of academic affairs and curriculum, and students are the research subjects. It is qualitative research with a phenomenological research type and purposive sampling technique. The results of this study show: i) the practice of differentiated learning in sociology subjects in high schools has been well implemented with the independent curriculum approach; ii) the challenges and obstacles faced by sociology teachers when implementing differentiated learning are the teacher’s skills in preparing learning; and iii) sociology teachers who face challenges and obstacles when implementing differentiated learning must pay more attention to the readiness of differentiated skills.